E-PERCEIVED VALUE AND E-PERCEIVED RISK ON E-LOYALTY WITH E-COMMERCE AS A MODERATING VARIABLE IN CONVENTIONAL BANKING (PRIVATE BANKS) IN INDONESIA - Nurul Kholifah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The era of Digitalization 5.0 has brought significant changes in digital consumer behavior, particularly in Indonesia's conventional banking sector. Digital banking transaction values have reached Rp72,000 trillion with growth exceeding 11% year-over-year. However, approximately 37% of millennial customers are ready to switch to other banks if digital services become more efficient or offer greater added value. This research analyzes the influence of E-Perceived Value (EPV) and E-Perceived Risk (EPR) on E-Loyalty (ELOY) with E-Commerce (ECOM) as a moderating variable in conventional private banks in Indonesia. The research employs a quantitative explanatory method with 250 respondents who are digital banking service users. Structural Equation Modeling (SEM) analysis results demonstrate that EPV has a significant positive effect on ELOY (β = 0.497; p < 0.001), EPR has a significant negative effect on ELOY (β = -0.10; p < 0.01), and ECOM acts as a moderating variable that strengthens the EPV-ELOY relationship (β = 0.128; p < 0.01) while weakening the EPR effect on ELOY. The model demonstrates excellent goodness-of-fit with Chi-square = 125.684 (p-value = 0.254 > 0.05), RMSEA = 0.018 (< 0.05), and CFI = 0.957 (> 0.90). These findings provide strategic implications for bank management in building digital customer loyalty through enhanced perceived value, risk minimization, and strong e-commerce service integration.